MYOSTATIN MODULATION BY MOTS-C MAY LEAD TO BENEFICIAL EFFECTS IN MUSCLE AND FAT TISSUE. (16th November 2018) - Ligeiro Coelho, A; Kim, S; Wan, J; Oliveira, P; Cohen, P
Abstract: Recently, mitochondrial-derived peptides (MDP) encoded as mitochondrial open reading frames have been identified. One of them, MOTS-c, acts as a systemic hormone and has been implicated in metabolic homeostasis, including through the regulation of muscle and fat metabolism. During aging, metabolic disruption is also associated with the onset of sarcopenia. Myostatin, a negatively regulator of skeletal muscle mass, plays a central role in this disease. To further understand the beneficial metabolic effects of MOTS-c, C57/B6 mice were injected daily, IP, with 5 mg/kg of MOTS-c. Skeletal and heart muscle, white adipose tissue (WAT) and plasma samples were collected and myostatin and other important WAT browning transcripts were analyzed by ELISA or qPCR. The results showed that MOTS-c treatment decreased myostatin levels in plasma and skeletal muscle (p<0.05). However, no alterations were detected in heart muscle. After 3 days MOTS-c treatment, the thermogenic UCP1, as well as other browning fat markers (Cidea, PGC-1, Era2 and Tbx1) were tendentially or significantly increased in WAT. The effect on markers were reversed after 8 weeks of injection, nevertheless UCP1 transcripts were increased further (p<0.05). MOTS-c treatment leads to a decrease in the systemic and tissue specific levels of myostatin, which may block the weakening of muscle strength. This potential double side effect of MOTS-c in skeletal muscle and WAT could be an important target in aging-related diseases. The enhancement of energy expenditure via increasing muscle mass and browning of WAT by MOTS-c may be essential in the protection against common diseases in elderly.